The Effect of Digital Transformation on the Information Access Gap for the Elderly in Makassar City - Allisa Qotrunada Munawaroh; Muchamad Zaenuri (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study examines the impact of digital transformation on the gap in access to information among the elderly in Makassar City. The study focuses on three main variables: access to technological devices, frequency of use of digital services, and digital skills. This study involved 100 elderly respondents who were selected using a simple random sampling technique. The results show that these three variables significantly affect the information gap, with digital skills having the greatest impact. Elderly people with high digital skills are better able to access, understand, and use digital information for daily needs, while limited access to technological devices and low frequency of digital service use exacerbate the information gap. The practical implications include the urgent need for the government and stakeholders in Makassar City to design policies that support the digital literacy of the elderly through community-based training, affordable digital devices, and the improvement of inclusive technological infrastructure. Future research should expand geographic and demographic coverage, integrate qualitative methods, and evaluate the effectiveness of digital literacy programs in addressing information gaps.